Pengaruh Kualitas Pelayanan dan Nilai Pelanggan Terhadap Kepuasan Pelanggan Pada Veranda Cafe - Dharmawangsa Pemayun, Tjokorda Gede Indra; Sudiksa, Ida Bagus (E-Jurnal Manajemen, 2014)
The purpose of this study was to determine the effect of service quality and customer value on customer satisfaction in the Veranda Cafe. This study used a qualitative research using surveys and questionnaires to 120 respondents. This study uses data analysis techniques of multiple linear regression. It was found that the variables of service quality and customer value and significant positive effect on customer satisfaction simultaneously at the Veranda Cafe. Furthermore, variable service quality and customer value and significant positive effect on customer satisfaction partially on the Veranda Café.
Keywords: Kualitas Pelayanan; Nilai Pelanggan; Kepuasan Pelanggan